Outpatient Medical E-Resume in Support INA-CBGs Claims for Covid-19 Patients at Hospital - Fitria Santika; Nurul Azmi Gumanti; Leni Herfiyanti; Candra Mecca Sufyana (MATRIK : Jurnal Manajemen, Teknik Informatika dan Rekayasa Komputer, 2021)
The lack of information needed to fulfill the claim requirements of Indonesia Case-Based Group (INA-CBGs) for Coronavirus Diseases (Covid-19) outpatients caused claim disputes, thus hampering the claim process for Covid-19 patients at Hospital. The existence of an electronic medical resume is believed to be a solution and make the claim process more effective. This study aimed to produce an electronic-based outpatient medical resume that fits the needs of Hospital X. The prototype method was chosen because it is suitable for developing systems quickly, and the results are easier to adjust because Hospital X can provide input in the system development process. Based on system testing using the black-box method, the medical e-resume system developed has overcome dispute claims at Hospital.